JAMINAN HUKUM TERHADAP WAJIB PAJAK DALAM PENYELESAIAN SENGKETA PAJAK - Liberthin Palullungan; Ririn Thomas (Paulus Law Journal, 2021)
In the life of the state, where there is a relationship between humans and humans, there are always rules that bind it, namely the law. Law regulates human rights and obligations. The purpose of this study is to find out what factors can hinder the process of resolving tax disputes. This research uses type. This study uses a type of normative juridical research sourced from primary and secondary materials, which were analyzed qualitatively by descriptively describing the results of the existing data. The results of this study indicate that the factors that hinder the process of resolving tax disputes are factors in the administration sector, namely the existence of the first obligation of the Taxpayer to pay 50% (fifty percent) of the total tax payable. Then in the field of justice, namely regarding the obligation of judges to present the appellate party or defendant in examination at trial.